HUBUNGAN PERSEPSI MAHASISWA DENGAN STRES AKADEMIK DALAM PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - DWI SINTA RIZKI ARIANI (LPPMK STIKES Widyagama Husada, 2022)
ABSTRACT Ariani, Dwi Sinta Rizki. 2021. The Correlation of Student’s Perception with Academic Stress in The Implementation of Online Learning in The Covid-19 Pandemic on Semester II Students of Widyagama Husada School of Health Malang. Thesis. Nursing Study Program of Widyagama Husada School of Health Malang. Advisors: (1) Miftakhul Ulfa, S.kep., Ners.,M.Kep. (2) Waifti Amalia, S.ST., M.Keb. Background: Students as the most numerous individuals in educational institutions certainly feel the impact of the COVID-19 pandemic, where the learning system that is usually carried out face-to-face, either on campus or on practice location, has turned online. The stress experienced by the students during the study period may disturb students mindsets due to the complexity of the problems they face. The students are not only required to have technical expertise, but they are also required to have a certain attitude and mindsets so that the broad insights gained by students can be applied in their social environment. Objectives: To find out the correlation between student perceptions and academic stress in the application of online learning during the COVID-19 pandemic for second semester students of STIKes Widyagama Husada Malang. Research methods: The research design used in this study was descriptive correlation with a retrospective approach. The population in this study were second semester students of STIKes Widyagama Husada Malang. Samples were taken using a purposive sampling technique with a total of 80 respondents. Research result: The results of the research indicated majority of second semester students of STIKes Widyagama Husada Malang experienced mild academic stress. Conclusion: There is a correlation between student perceptions and academic stress in the application of online learning during the COVID-19 pandemic for second semester students of STIKes Widyagama Husada Malang. References: 32 References (2010-2020) Keywords: Student Perception, Academic Stress, Online Learning